What influence does resistance exercise order have on muscular strength gains and muscle hypertrophy? A systematic review and meta-analysis - Nunes, J. P.; Grgic, J.; Cunha, P. M.; Ribeiro, A. S.; Schoenfeld, B. J.; de Salles, J. F.; Cyrino, E. S. (European Journal of Sport Science, 2021)
The objectives of this paper were to: (a) systematically review studies that explored the effects of exercise order (EO) on muscular strength and/or hypertrophy; (b) pool their results using a meta-analysis; and (c) provide recommendations for the prescription of EO in resistance training (RT) programmes. A literature search was performed in four databases. Studies were included if they explored the effects of EO on dynamic muscular strength and/or muscle hypertrophy. The meta-analysis was performed using a random-effects model with Hedges` g effect size (ES). The methodological quality of studies was appraised using the TESTEX checklist. Eleven good-to-excellent methodological quality studies were included in the review. When all strength tests, that is, both in multi-joint (MJ) and single-joint (SJ) exercises were considered, there was no difference between the EOs (ES = -0.11; p = 0.306). However, there was a difference between the MJ-to-SJ and SJ-to-MJ orders for strength gains in the MJ exercises, favouring starting the exercise session with MJ exercises (ES = 0.32; p = 0.034), and the strength gains in the SJ exercises, favouring starting the exercise session with SJ exercises (ES = -0.58; p = 0.032). No significant effect of EO was observed for hypertrophy combining site-specific and indirect measures (ES = 0.03; p = 0.862). In conclusion, increases in muscular strength are the largest in the exercises performed at the beginning of an exercise session. For muscle hypertrophy, our meta-analysis indicated that both MJ-to-SJ and SJ-to-MJ EOs may produce similar results.